The incidence of recurrence after Delorme's procedure for full thickness rectal prolapse - a retrospective private-public cohort study - Plaskett, Jeremy John (Department of Surgery, 2017)
Background: Delorme's perineal repair has remained a procedure reserved for full-thickness rectal prolapse in elderly or co-morbid patients due to its low morbidity and complications. Reported recurrence rates are higher than in abdominal approaches. Aim: The study assesses long-term outcomes after Delorme's procedure (DP), specifically recurrence and postoperative bowel function, in both a multi-surgeon public hospital and a single surgeon cohort in the private sector (Groote Schuur Hospital and Kingsbury Hospital). Patients and Methods: This retrospective cohort study includes all patients who underwent DP between February 2001 and March 2014 at both study sites. The primary outcome was absence of recurrence. Secondary outcomes were bowel function (incontinence and constipation), postoperative mortality and morbidity and length of hospital stay. Patient data was collected from electronic records (Kingsbury Hospital) and paper folders/op notes (Groote Schuur Hospital) and current status was acquired by telephonic interview with either the patient, a family member or caregiver, as appropriate. Results: Seventy patients underwent DP: 37 private and 33 public, mean age 71yrs. There were 16 (23%) recurrences (7 private, 9 public), of which 8 (11%) underwent reoperation. Mean time to recurrence was 30 months (48 private; 15 public). There were 2 postoperative deaths (pneumonia, myocardial infarction), 6 major complications (rectal bleeding requiring transfusion or reoperation, bowel obstruction, pneumonia, myocardial infarction), and 6 minor complications (rectal pain, rectal bleeding not requiring reoperation or transfusion, urinary retention, confusion, hyponatraemia). The mean postoperative hospital stay was 4 days. Conclusion: Long-term outcome from this large series compares favorably with most other published series, specifically a low recurrence rate. Proposed reasons for this will be presented, within the context of the published literature.